Study on Tooth Surface Roughness Modeling of Form Grinding Considering the Change of the Local Grinding Condition - Chen Xiaoqi; Tang Cheng; Liao Xianggui; Zhou Weihua; Tang Jinyuan (Jixie chuandong)
Modeling gear grinding surface roughness is an essential basis for understanding gear integrity. Due to the complex macro shape of the grinding wheel and workpiece and the difference in local grinding conditions during gear grinding, the direct transfer of the classical surface grinding roughness modeling method is limited. Therefore, this study proposes a method for modeling the surface roughness of gear form grinding, considering the variation of local grinding strips. According to the grinding mechanism of form grinding, the grinding motion relationship between the grinding wheel and the gear is analyzed. The motion trajectory equation of abrasive particles at different local positions under the influence of macro geometric shapes is derived. A grinding wheel model considering the random distribution characteristics of abrasive particles in the complex shape of grinding wheel is established. Based on the generation mechanism of grinding surface roughness, the surface roughness of formed grinding teeth is obtained by an iterative algorithm. The forming grinding test of 12Cr2Ni4A gear material after carburizing and quenching is carried out. The results show that the prediction model of the surface roughness of formed grinding teeth presented in this study agrees with the experimental results. The model can well reflect the surface roughness distribution along the tooth profile under the local grinding strip difference. The work of this study puts forward a new understanding of the formation mechanism of the surface roughness of the formed grinding teeth and provides more reference and basis for the follow-up research.